(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article provides an in-depth analysis of the theoretical foundations, methodological strategies, and practical outcomes of the STEAM (Science, Technology, Engineering, Arts, Mathematics) approach in education. The main objective of the study is to examine successful STEAM integration practices and statistical indicators from European countries and to identify the possibilities for implementing these mechanisms within the education system of Uzbekistan. Drawing on international reports (OECD, UNESCO, World Bank) and research conducted by leading universities (MIT, Harvard), the article offers scholarly conclusions on the role of interactive teaching methods, project-based learning, and multimedia tools in developing learners’ creative thinking, critical analysis, and practical skills.